Three new Canuellidae (Copepoda: Canuelloida) from Iran - Nazari, F.; Mirshamsi, O.; Sari, A.; Aliabadian, M.; Arbizu, P. Martínez (Zootaxa, 2018)
A survey of copepods from intertidal zone of the Persian Gulf and the Gulf of Oman resulted in discovery of three new species belonging to the family Canuellidae Lang, 1944. This work contributes to the final aim to describe meiobenthic copepods from this region and is the first description of meiobenthic copepods from Iranian coastline. The new species belong to the genera Brianola Monard, 1926, Canuella, T. & A. Scott, 1893, and Scottolana Huys, 2009. Compared to other congeners, Brianola haliensis sp. nov. is unique in the armature of the first leg, number of segments and setation of the antennary endopod and exopod. Canuella persica sp. nov. is easily distinguishable from its congeners by the shape of furcal rami and male genitalia. Scottolana gomezi sp. nov. is assigned to the longipes-group by the presence of two and three post-genital somites in the female and male, respectively. It is closely related to S. geei (Mu & Huys, 2004) recorded from the Bohai Sea, China, but can be distinguished by its eight-segmented antennary exopod, mouthparts setation, and shape of the furcal rami.